Fire in the Wildland-Urban Interface: Selecting and Maintaining Firewise Plants for Landscaping - J. Douglas Doran; Cotton K. Randall; Alan J. Long (EDIS)
This extension publication outlines plant characteristics that have the greatest effect on flammability, as discussed at three levels: plant parts (primarily leaves), whole plants, and groups of plants. Selecting firewise plants can reduce wildfire risk, but during drought conditions, most plants will burn if exposed to enough heat, regardless of their flammability. This document is Circular 1445, one of the series Fire in the Wildland-Urban Interface of the School of Forest Resources and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: March 2004.